2020
DOI: 10.1080/24749508.2020.1754705
|View full text |Cite
|
Sign up to set email alerts
|

Active tectonics deduced from geomorphic indices and its implication on economic development of water resources in South-Eastern part of Mikir massif, Assam, India

Abstract: The geomorphic analysis of mountain fronts and related drainage networks can provide valuable insights about the recorded tectonic history of any given region especially when the area shows higher seismic activity in recent times. Therefore, such studies at a regional scale have been frequently undertaken using morphotectonic analysis to delineate areas having higher tectonic activity. Also, study of active tectonics in an area is very important for any development activity especially hydropower projects as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The differences in the S L values indicate changes in the longitudinal profile of a stream and hence reflect the possible tectonic activity. Baruah et al (2020) concluded that both stream length gradient index (SL) and steepness index (SI) have their common genetic relationship between the surface uplift and response of any channel gradient to it.…”
Section: The Geomorphic and Geological Parametersmentioning
confidence: 99%
“…The differences in the S L values indicate changes in the longitudinal profile of a stream and hence reflect the possible tectonic activity. Baruah et al (2020) concluded that both stream length gradient index (SL) and steepness index (SI) have their common genetic relationship between the surface uplift and response of any channel gradient to it.…”
Section: The Geomorphic and Geological Parametersmentioning
confidence: 99%
“…The Fold and Thrust Belt was studied extensively in terms of regional geology and tectonics (e.g., Hossain et al, 2019; Khan, 1991; Najman et al, 2012; Reimann, 1993), structures (e.g., Hossain, 1985; Hossain & Akhter, 1983; Hossain et al, 2019; Rahman et al, 1985), and stratigraphy and sedimentology (e.g., Alam et al, 2003; Alam & Ferdous, 1995; Gani & Alam, 1999; Rahman et al, 2017; Sultana & Alam, 2000). Although numerous studies used river longitudinal profile and geomorphic index analyses to understand the feedback between tectonic uplift, erosion, climate, lithology, and deformation in the northern part of the Basin such as the Shillong Plateau, western and eastern syntaxis regions, Lesser Himalayas, and the Siwalik Foreland Basin, the interplay of tectonics and river‐dominated landscape evolution of the Basin is poorly known (e.g., Wobus et al, 2006; Harkins et al, 2007; Aiken & Brierley, 2013; Ambili & Narayana, 2014; Goswami & Pant, 2019; Strong et al, 2019; Topal, 2019; Kothyari et al, 2020; Kumar & Duarah, 2020; Bhattarai et al, 2021, Baruah et al, 2022; Figure 1a). Therefore, the key objective of this paper is to decipher an independent perspective of the rivers' response to the tectonic activity which includes: (i) constraining bedrock river perturbation by analysing stream longitudinal profiles using quantitative morpho‐tectonic analysis of geomorphic metrics, and (ii) mapping and characterizing unmapped geologic lineaments.…”
Section: Introductionmentioning
confidence: 99%
“…[14] calculated different morphotectonic indexes to examine the tectonic signals in the Carpathian mountain massif region in Poland. In addition, seismic hazards assessment of active spots was examined by many researchers [17][18][19], while others applied the advanced tools to provide insight into the analysis of geological hazards in arid regions [20,21]. For example, authors in ref.…”
Section: Introductionmentioning
confidence: 99%
“…For example, authors in ref. [18] attempted to assess the tectonic activity of Mikir massif in India, and they modelled an assessment for irrigation and hydropower development of the study area; on the other hand, authors in ref. [20] established a hydraulic and hydrologic model for the Ayamama River in Turkey.…”
Section: Introductionmentioning
confidence: 99%